Communication and organizational changemaking for diversity, equity, and inclusion a case studies approach - Austin, Jasmine T.; Bruscella, Jaqueline S.; Van Gilder, Bobbi J. (Routledge, Taylor & France Group, 2024)
This book explores the opportunities, challenges, and effective approaches to organizational change regarding diversity, equity, inclusion, and belonging. Featuring application-based case studies and practical guidelines for meaningful organizational change, this book problematizes some of the current DEI initiatives in today's organizations. It examines multiple forms of diversity (e.g., race, age, mental health) from a variety of perspectives (e.g., leadership, employee), with case studies that demonstrate how changemaking efforts can be reimagined and implemented in better, more nuanced, and more sustainable ways to produce meaningful organizational change. Through these case studies, readers learn from organizations' successes and failures in their attempts to implement DEI practices. Each chapter concludes with explicit practical implications and/or actionable recommendations for organizational changemaking. This text will make an impactful addition to courses in communication and diversity or organizational communication/change at the advanced undergraduate or graduate level and will be an essential guide for professionals wishing to lead change in their organizations"--